MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN SENI TARI MELALUI MEDIA AUDIO VISUAL DI SMPN 34 PADANG - Sari, Julia Puspita; Astuti, Fuji (SENDRATASIK UNP, 2019)
AbstrakThis study aims to improve students learning outcomes in learning Dance in SMP Negeri 34 Padang. This study belongs to the type of classroom action. The study instruments were written tests and observation sheets. The procedures of this studywere preliminary study and cycle 1.Techniques of Data collection were carried out by doing observation, interview and literature study. The collected data were analyzed by using the percentage formula. The result shows that the use of audiovisual media in learning dance can improve the students learning outcomes at class VIII.7 in SMP N 34 Padang. It is also easy for the students to remember every material that is presented because they have watched through the audio visual media that is used by the teacher. The students activity in cycle 1 is 48.3% while in cycle 2, it increases in the students activity is quite high with a percentage is 78.9%. The learning outcomes in cycle 1 are still low with an average test score is 62.8% with a percentage of completeness is only 48.3%. After reflecting in cycle 2,it increases in the students learning outcomes has an average value of learning outcomes that is 78.9% with a percentage of completeness is 83.2%.Â Keywords:Improving, Learning Outcomes, Dance, Audio Visual Media